Mental stress and fast-food consumption as determinants of early hypertension among students: A Qualitative Study - Cipto Susilo; Ari Setyawati; Indrawati Aris Tyarini; Matilda Martha Paseno (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Hypertension is a major global public health problem affecting more than 1.2 billion people worldwide and contributing substantially to cardiovascular morbidity and premature mortality. Recent evidence indicates a rising trend of elevated blood pressure among young adults, particularly in low- and middle-income countries experiencing rapid lifestyle and dietary transitions. University students are increasingly exposed to chronic academic stress and easy access to high-sodium fast food, potentially accelerating early cardiovascular risk. However, limited qualitative evidence integrates psychosocial and dietary determinants of early hypertension within student populations. Research Methodology: This qualitative study employed a phenomenological approach to explore students lived experiences related to mental stress, fast food consumption, and perceived early hypertension risk. The study was conducted at a public university in Indonesia between March and June 2025. Twenty undergraduate students aged 18–25 years were recruited using purposive maximum variation sampling. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis following Braun and Clarke’s framework. Data saturation was achieved at the 18th interview and confirmed in subsequent interviews. Results: Four major themes emerged: (1) academic and psychosocial stress as persistent pressure; (2) fast food as a stress-driven coping mechanism; (3) limited awareness of early hypertension risk; and (4) the interconnection between stress, diet, and physical symptoms. Participants described chronic stress leading to frequent fast-food consumption, which was perceived to contribute to headaches, palpitations, and fatigue. A knowledge behavior gap was evident, as awareness did not translate into preventive action. Conclusion: Early hypertension risk among students is shaped by the interaction between psychosocial stress and maladaptive dietary coping behaviors. Integrated campus-based strategies incorporating stress management, healthier food environments, and routine blood pressure screening are essential to prevent long-term cardiovascular disease